Unveiling the Factors Influencing U.S. Consumer Adoption of the Apparel Digital Retail Theater - Yi-Ning Tai; Ting Chi (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
In recent years, the fashion industry has undergone a significant transformation driven by digital innovations, particularly with the emergence of the digital retail theater (DRT). A DRT integrates augmented reality (AR), virtual reality (VR), and 3D modeling to create immersive shopping experiences that bridge the physical and digital worlds. This study specifically focuses on apparel DRTs and investigates the key factors influencing U.S. consumers’ intention to adopt this technology. Drawing on the unified theory of acceptance and use of technology (UTAUT) and perceived risk theory, we developed and tested an integrative research model. Primary data were collected through a structured online survey administered via Amazon Mechanical Turk (MTurk). A total of 400 valid responses were obtained from U.S. consumers. Data were analyzed using multiple regression analysis to examine the hypothesized relationships. The results indicate that effort expectancy (ease of use), facilitating conditions (technical infrastructure), physical risk (concerns about potential harm), and time/convenience loss risk significantly influence consumers’ intention to adopt apparel DRTs. Surprisingly, performance expectancy and social influence were not significant predictors of DRT adoption. These findings provide valuable insights for apparel retailers, emphasizing the importance of user-friendly designs, robust technical infrastructure, and minimizing perceived risks to foster DRT adoption.